"Fearfully and wonderfully made": Black Caribbean women and the decolonization of thick Black female bodies. (August 2020) - Gentles-Peart, Kamille
Black feminists promote decolonization as a strategy to recuperate Black women's dignity and humanity from racist colonialist ideologies. In order to fully explore Black women's emancipation, Black feminists have to explicitly consider how Black women break away from the ways in which thick Black female bodies have been defined by dominant white colonial cultures, and how Black women of different ethnicities engage in their own recovery of voluptuous Black female bodies. In this paper, I use a Black feminist intersectional lens to explore the ways in which Black Caribbean women recuperate thick Black female bodies from colonialist and racist ideologies. Specifically, using focus groups, I examine how these women participate in what I refer to as emancipatory thick body politics, discourses that challenge and resist the dehumanization of thick Black female bodies. Findings indicate that Black Caribbean women actively participate in decolonizing thick Black female bodies by forming sisterhood communities with other Black Caribbean women, re-defining womanhood, and engaging in transgressive interpretations of Christian doctrine.